Satanic feminism: Lucifer as the liberator of woman in nineteenth-century culture - Faxneld, Per (Oxford studies in western esotericism, 2017)
The notion of woman as the Devil's accomplice is prominent throughout Christian history and was used to legitimise the subordination of wives and daughters. In the 19th century, rebellious females performed counter-readings of this misogynist tradition and Lucifer was reconceptualised as a feminist liberator. Per Faxneld shows how this surprising Satanic feminism was expressed in a wide range of 19th-century texts and artistic productions